The Gender Employment Gap: Costs and Policy Responses - Martina Bisello; Massimiliano Mascherini (Intereconomics, 2017)
This paper will firstly investigate the economic and the social costs associated with the observed gender employment gap. It will then discuss key aspects of the needed policy responses to foster and promote labour market participation among women.
Keywords: 330